PENGARUH SUMBER PENDAPATAN DESA TERHADAP KESEJAHTERAAN MASYARAKAT: (Studi Kasus Di Desa Kertaraharja, Desa Bojong, Desa Cikembar, Kecamatan Cikembar Kabupaten Sukabumi) - Ramdani, Ai Sahri (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
This study aims to determine the effect of village income sources on community welfare. There are seven sources of village revenues: PADes, APBN, tax and retribution revenue sharing, ADD, budget and expenditure assistance, Grants and Donations, and other legitimate village revenues. With the largest revenues sourced from the state budget. With such a budget the village government is mandated to be able to prosper the community. To measure the welfare of the community, seen from the index of village independence, this index has three dimensions, namely, own ability index, joint responsibility index, and sustainability index. Furthermore, the independence of the village becomes a benchmark for how the village government can increase the productivity of the community to achieve the welfare objectives of the village community. Variables used in this research are village income and community welfare. This study uses a method of quantitatif, descriptive associative. The sample of this research is village staff, BPD, RT, and RW in Kertaraharja Village, Bojong Village, and Cikembar Village with 70 respondents. The data collection tool is a questionnaire with an ordinal scale (Likert). Based on the results of hypothesis testing using a t-test, the source of income of the village has a positive effect on the welfare of the community in Kertaraharja Village, Bojong Village, and Cikembar Village, Cikembar District, Sukabumi District, showing a positivity of 5,741.